Students’ Perception of Online Assessment and Its Influence on Their Learning Achievement - Reza Faizaturrohmah; Semi Sukarni; Abdul Ngafif (Scripta : English Department Journal, 2022)
This research aimed at knowing the students’ perception on online assessment of English subject during Covid-19 pandemic and the influence of online assesment on learning achievment of the students at grade X Mechanical Engineering at SMK N 2 Kebumen. This research uses mixed method. The population of this study is 108 students, and the researcher used purposive sampling to select 72 students as the sample.Research data obtained with the interview, questionnaire and documentation. The result of the mean score of students’ perception of online assessment in tenth grade students of SMK N 2 Kebumen was 74.53 which is categorized as “good”, whereas the mean score of students’ English achievement was 81.81 which is categorized as “excellent. Based on the calculation the value of r is lower than r table (0.059) < (0.235). It means that the students’ perception of online assessment does not influence on students’ achievement of English subject during Covid-19 pandemic in X grade students of SMK N 2 Kebumen. The coefficient determination R2 is 0.000. It implied that students’ perception does not contribute to the students’ English achievement (0%).